PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI BANGUN DATAR KELAS II UPT SD NEGERI DOROMUKTI - Ayunda Dewi Puspita; Wendri Wiratsiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this research is to determine the implementation of the Problem-Based Learning model to improve math learning outcomes on the topic of flat shapes for second-grade students at UPT SD Negeri Doromukti. The applied approach is Classroom Action Research (CAR) using the Kemmis and McTaggart model implemented in 2 cycles. Each cycle involves four main stages: planning, action, observation, and reflection. The research targets include second-grade students at UPT SD Negeri Doromukti, and the information collection process is carried out using observation and test techniques. Based on preliminary observations, it is known that the teacher still predominantly uses the lecture method. The data obtained show that the implementation of the Problem-Based Learning model can improve learning outcomes. This is evidenced in cycle 1, where 8 students reached the Minimum Passing Criteria (KKTP) with an average score of 70, followed by cycle 2, where there was an increase with 10 students meeting the KKTP with an average score of 80, thus it can be concluded that the desired target has been achieved, which is a minimum average score of 75.